Ultrasound-Enhanced Tumor Penetration of Carrier-Free Nanodrugs for High-Efficiency Chemo-Photodynamic Therapy of Breast Cancer - Yun Xiang; Shiyu Liang; Ping Wang (Journal of Functional Biomaterials)
In recent years, chemo-photodynamic combinational therapy has become increasingly popular in treating breast cancer. However, the limited accumulation of nanodrugs into tumors (less than 1% of the injected dose) impacts therapeutic efficacy to an extreme extent. Herein, the photosensitizer Chlorin e6 (Ce6) and the chemotherapeutic drug rhein were self-assembled to form a carrier-free nanodrug (RC NPs) with good stability and a high drug loading rate (nearly 100%). In vitro, the phototoxicity of RC NPs resulted in a mere 17.8% cell viability. Ultrasound (US) irradiation was applied to increase the permeability of tumor blood vessels, thus greatly enhancing the drug accumulation of RC NPs in tumor tissues (1.5 times that of the control group). After uptake by tumor cells, Ce6 could produce a significant amount of reactive oxygen species (ROS) when exposed to laser irradiation, while rhein could inhibit tumor cell proliferation and affect mitochondrial membrane potential, inducing tumor cell apoptosis through the mitochondria-dependent apoptosis pathway, thus effectively realizing the combined effect of PDT and chemotherapy. The final tumor inhibition rate reached 93.7%. Taken together, RC NPs strengthen the enhanced permeability and retention (EPR) effect when exposed to US irradiation and exhibit better tumor suppression, which provides new insights into chemo-photodynamic combination treatment for clinical breast cancer.